Automação de sistemas utilizando as linguagens de comandos elétricos e ladder - CONCEIÇÃO, Hugo da Rocha (2019)
This work the first indications, contextualization, history, concepts, techniques and evolutions of automation are presented. The main objectives of this work are the automation of six processes, and present the main programming challenges faced in each process, as well as the techniques and solutions used to overcome such challenges. The processes to be automated are as follows, electric gate, industrial silo, group compressors, traffic signaling, industrial mixer and a bottle processing line, these are automated through two programming languages, these are the language of electrical commands and the language of PLC (Ladder), the first one is developed through CADe_SIMU software while the Ladder language is worked through the software LogixPro.